Consumer Behavior with Social Media Introduction to the Study - Rojsurakitti, Terdsak (Archives of Business Research, 2015)
Normally, people are rely on trust and familiarity as the primary way to reduce social uncertainty. In term of e-commerce, nature of business is unfamiliar with customer and one-time purchase. It is not interaction process. Therefore, people sometimes are entrusted to them. Among Asian people, familiarity is the primary concern of our culture. People behavior is tending to believe in whatever their familiar person says. That why many direct approach to consumers. Online also can use this trust to do e-commerce since there are some room for merchants can do on some website. Hence, social media come to play as important role on connecting people together through online. We can give definition to social media as group of application that use among the specific categories by characteristics, collaborative projects, blogs, social networking site, content communicates, virtual game, etc. Finally, we come to analyze the factors why people in Thailand especially in Bangkok use purchase the products through social media and trigger how to use this one as good pieces of work for business. Keywords: Social Media, People behavior, e-commerce, People behavior, online, website